2010
DOI: 10.1007/s00192-010-1152-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for overactive bladder symptoms after pelvic organ prolapse surgery

Abstract: Introduction and hypothesisThis study focussed on the factors which predict the presence of symptoms of overactive bladder (OAB) after surgery for pelvic organ prolapse (POP).MethodsConsecutive women who underwent POP surgery with or without the use of vaginal mesh materials in the years 2004–2007 were included. Assessments were made preoperatively and at follow-up, including physical examination (POP-Q) and standardised questionnaires (IIQ, UDI and DDI).ResultsFive hundred and five patients were included with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
5
37
1
2
Order By: Relevance
“…A possible explanation for this finding is that women after prolapse surgery achieved de novo urgency, as was found in 5% of the patients in one study [28]. …”
Section: Discussionmentioning
confidence: 92%
“…A possible explanation for this finding is that women after prolapse surgery achieved de novo urgency, as was found in 5% of the patients in one study [28]. …”
Section: Discussionmentioning
confidence: 92%
“…Similarly, prolapse repairs alone have shown improvement in OAB symptoms (10, 11, 12, 13, 14). However, whether that same effect can be seen in women receiving slings and undergoing complex prolapse surgery is not as well defined.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that prior pelvic and reconstructive surgeries may denervate the bladder [28,29]. Patients who underwent a hysterectomy may experience OAB symptoms postoperatively due to the disruption of autonomic nerve fibers running along the pelvic plexus.…”
Section: Discussionmentioning
confidence: 97%